Role of inflammatory mediators in priming, activation, and deformability of bovine neutrophils - McClenahan, D.; Fagliari, J.; Evanson, O.; Weiss, D. (Amer Veterinary Medical Assoc, 2000)
Objective-To determine the capacity of inflammatory mediators tumor necrosis factor-alpha (TNF-alpha), interleukin-8 (IL-8), platelet-activating factor (PAF), lipopolysaccharide (LPS), and leukotoxin to prime, activate, or alter deformability of adult bovine neutrophils.Sample Population-Blood collected from 5 healthy adult Holstein cows.Procedure-Isolated neutrophils or whole brood was incubated with TNF-alpha, IL-8, PAF, LPS, or leukotoxin, and neutrophil chemiluminescence, degranulation, deformability, shape change, CD11b expression, and size distribution was measured.Results-incubation with TNF-alpha, IL-8; PAF, and IFS primed neutrophils for oxygen radical release but caused minimal oxygen radical release by themselves. None of the inflammatory mediators induced degranulation. Incubation with TNF-alpha and PAF resulted in a decrease in neutrophil deformability and induced shape change in neutrophils. incubation with PAF consistently resulted in an increase in neutrophil size as measured by use of flow cytometry. Only IL-8 caused an increase in expression of CD11b by neutrophils.Conclusions and Clinical Relevance-Inflammatory mediators tested had minimal effects on neutrophil oxygen radical production or degranulation but did prime neutrophils for oxygen radical production. Incubation with PAF and TNF-alpha caused a decrease in neutrophil deformability and altered neutrophil shape and size. Results of our study indicate that PAF- and TNF-alpha-induced changes in neutrophil deformability and size may cause integrin- and setectin-independent trapping of neutrophils in the lungs of cattle with pneumonic pasteurellosis.